(untitled) (Jurnal Proaksi, 2023)
Abstract Tax aggressiveness is a factor causing delays in tax revenue or tax evasion efforts carried out by legal and illegal means. The legal way is by tax planning and tax avoidance, while the illegal way is by tax evasion. This study aims to examine the effect of Leverage and Profitability on Tax Aggressiveness. In this study, the sample used was conventional commercial banks listed on the IDX with research periods before and after the COVID-19 pandemic, namely 2019, 2020, and 2021. The sampling technique used was purposive sampling. The data analysis method in this study is panel data regression analysis using Eviews version 10. The simultaneous test and partial test results show that the variables of Leverage and Profitability have an effect on tax aggressiveness. Leverage has no significant negative effect while profitability has significant positive effect on tax aggressiveness Keywords: Profitability, Leverage (DER), Tax Aggressivenes